The Relationship Between Discipline with Student Learning Outcomes of Equality Education Program (Universitas Negeri Semarang, 2022)
Some students pursuing the C PKBM Sumber Ilmu program still get learning outcomes under the KKM. These problems are caused by several factors, one of which is the discipline factor. Therefore, related to this problem, there is a view that disciplinary attitudes may have an effect on achieving success in student learning. The purpose of this study was to determine the relationship between discipline and learning outcomes of students in the Sumber Ilmu PKBM paket C equivalence program and to determine how large the relationship between discipline and student learning outcomes in the Sumber Ilmu PKBM paket C equivalence program. The number of samples in this study is a total population of 60 students. Data collection techniques using questionnaires and documentation. The results of this study are that there is a significant relationship between discipline and student learning outcomes in paket C. The results indicate a strong relationship between discipline and learning outcomes for students in paket C, which is in the range of 0.60 – 0.799, so the alternative hypothesis (ha) is accepted. Suggestions for students to improve their disciplined attitude in learning activities to get maximum results. The thing that distinguishes this research from other research is that the researcher wants to know the renewal of the process of acquiring learning outcomes for students on the disciplined attitude of students in paket C in PKBM Sumber Ilmu.